Célula de comutação óptica em cristal fotônico - Lima Júnior, Almir Wirth (2010)
We present the complete cycle of projects, and analysis of optical directional couplers embedded in photonic crystals (PhCs), and selected the more appropriate PhC coupler to operate in all-optical switches in the bands C, L, and U of the ITU (1530 - 1675nm). We analyze and propose an all-optical switching cell based on directional coupler embedded in photonic crystal (PhC), which is driven by an external command signal. In order to obtain the lowest possible coupling lengths we analyzed several projects of such devices. The analysis of these different projects demonstrated the dependence of the coupling length and of the operating range, regarding to the radius of the dielectric rods of the interfaces and of the coupler central region. Finally, we showed all the details of the directional coupler more suitable for operation as switching cell in an all-optical switch worwing over the C, L, and U bands of the ITU. This switching cell is controlled by an optical external command signal, which has relatively low optical power. The minimum coupling length of this device (bar state) is 37μm.